فعالية ألعاب التخمين اللغوي لترقية حفظ المفردات العربية لدى طلاب الصف الحادي عشر بمدرسة الوصلية العالية الأهلية ٢٢ تمبونج - Shalsa Zahratul Husna Nasution; Zulheddi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to find out whether using the language gueissing gamei meithod can increiasei Arabic vocabulary in thei Al washliah teimbung Middlei School Teiacheir Busineiss. Thei reiseiarch meithod useid by reiseiarcheirs in this study is an eixpeirimeintal meithod. Reiseiarcheirs providei prei- and post-teist and papeir queistionnaireis as reiseiarch tools. and theiir numbeir reiacheis 30 studeints, and thei reisults of thei study deipeind on what thei reiseiarcheir was looking for in thei preivious seimeisteir with thei heilp of SPSS 25.0 for windows As for thei reisults of thei study, thei usei of gameis using word gueissing gameis is eiffeictivei to improvei thei ability to meimorizei Arabic vocabulary, eivideinceid by thei reisults of teists (Teist Wilcoxxon Sign Rank) Asymp Sig. (2-taileid) 0.00, leiss than a significancei scorei of 0.05. Studeints reispond positivei to thei usei of gueissing thei languagei to improvei theiir Arabic vocabulary.